Enseñanza-Aprendizaje En La Estancia ClÃnica: Percepción Desde Los Estudiantes De Licenciatura En EnfermerÃa - Carrillo, Eliazar González; Pizarro, Norma; Sánchez, Oscar Joel Talavera; GarcÃa, Salvador Vargas (European Scientific Journal, ESJ, 2017)
The clinical teaching of nursing graduates is one of the fundamental pillars for the development of knowledge, skills, attitudes, and values that would be projected in the real scenarios of their disciplinary practice. The expectation of any institution in professional formation in health discipline is that the facilitator should create an environment that is favorable for an effective teaching-learning process to take place. During the stay of the students in the healthcare institution, it is essential that they acquire a prospective, sensitive, and a specialized vision about their practice and the challenges they face in an increasingly complex society. There are a number of contradictions between theory and practice in care. This, however, leads to a clear gap which becomes evident in traditional teaching models. This requires a redirection towards innovative, humanistic, and specialized approaches to more dynamic ones in this information/knowledge society. The objective of this study was to obtain the perception of undergraduate nursing students on clinical teaching and whether it is related to the hospital context, experience, and teaching profile. Therefore, this favors an effective learning process. It is a quantitative, non-experimental, analytical, descriptive, cross-sectional, and prospective study with a convenience sample of 212 students in a sixth, seventh, and eighth semester of the clinical stationed (practice) class. Among the most important results of the research, it was found that the students stated that there is no functional relationship between Jean Watson’s Human Care Theory and its application in the clinical field. They also perceived that this learning had a significant impact on several factors both of the Clinical environment and the educational institution. The study concludes that the students’ perception of the teaching learning process oscillates between the contradiction of a theory that cannot be projected in practice and a series of factors that have a negative impact on the formation of their professional competences